Reiter's disease in a 13-year-old girl - Alia Abbas Rizvi; Amrinder J Kanwar; Shitij Goel; Seema Dua (Wolters Kluwer Medknow Publications, 2016)
Reiter's disease or reactive arthritis is characterized by the classic triad of urethritis, arthritis, and conjunctivitis, usually following a genitourinary or gastrointestinal infection. Reiter's syndrome has been reported in children, but they usually do not manifest with the typical triad. Only a few such cases have been reported, and these have affected males predominantly. Furthermore, human leukocyte antigen B27 association in children is not well-established. However, in our case, it was positive. We, herein, report a case of a 13-year-old girl who presented with redness of eyes and joint pains followed by skin involvement is reported. She was managed with topical steroids and keratolytics along with oral nonsteroidal anti-inflammatory drugs and showed complete resolution in 3 weeks.